Answer:
Part A)
![\displaystyle z_6 = 9609600000x^(10)](https://img.qammunity.org/2023/formulas/mathematics/high-school/rth1l438iciw30wzqi4mqy864veb3ctcqg.png)
Part B)
![z_4 = 10500 x^9](https://img.qammunity.org/2023/formulas/mathematics/high-school/m0zl6h89ie4z4nhgs0juvlyp5bcgxbqxkj.png)
Explanation:
Recall the binomial expansion theorem:
![\displaystyle (x+y)^n = \sum_(k=0)^(n){n \choose k} x^(n-k) y^k](https://img.qammunity.org/2023/formulas/mathematics/high-school/ajx5q7fafsuwx78j6w6prnccpusqgj9qii.png)
Part A)
Our expression is equivalent to:
![\displaystyle (2x+5)^(15) = \sum_(k = 0)^(15) {15 \choose k} (2x)^(15-k)\cdot 5^k](https://img.qammunity.org/2023/formulas/mathematics/high-school/pkh5euqjzn5lcepo7azzuep5vopc9bfj5h.png)
To find the sixth term, let k = 5. Therefore, the sixth term is:
![\displaystyle \begin{aligned} z_6 &= {15\choose 5} (2x)^(15-5)\cdot 5^5 \\ \\ & = {15\choose 5}x^(10) \cdot (2)^(10)\cdot 5^5 \\ \\ &= 9609600000x^(10)\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/i7hdx53o8dpd89fis9jn0ub3g3jds5y1ip.png)
Part B)
Likewise:
![\displaystyle \begin{aligned} \left(x^2 + (5)/(x)\right)^9 = \sum_(k=0)^9 {9\choose k}(x^2)^(9-k)\left((5)/(x)\right)^(k)\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ragbfjgtdlmzmtw490pk6nu5qk97bhu9e3.png)
To find the fourth term, let k = 3. Therefore, the fourth term is:
![\displaystyle \begin{aligned} z_4 & = {9\choose 3}\left(x^2\right)^(9-3) \left((5)/(x)\right)^(3) \\ \\ & = {9\choose 3}x^(12) \cdot (5^3)/(x^3) \\ \\ & = 10500x^9\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/2u8nbywppvr2pfvhsq415pv485knhki9xf.png)